Análisis del desempeño innovador de las empresas de servicios intensivos del conocimiento - Del Carpio Gallegos, Javier Fernando (2024)
Objective. To evaluate the relationship between information sources and absorptive capacity and how this capacity improves a company's innovative performance. Methodology. The study presents evidence based on a sample of 212 Peruvian P-ESICs and 355 T-ESICs. The research applied a structural equation model approach using the AMOS software; while the PROCESS software was used for the mediation analysis. Results. It was found that when ESICs are exposed to internal, market, institutional, and other sources of information, they are in a better position to develop innovations. However, this condition is not sufficient, since it is necessary to develop dynamic capacity (called absorptive capacity). Conclusions. This study contributes to a better understanding of the innovative behavior of ESICs in an emerging economy such as Peru, since it takes into account that emerging economies have different characteristics than more developed economies. It was also verified that absorptive capacity does not mediate the relationship between information sources and innovative performance in the two groups of ESIC companies analyzed.